Prinsip dan Etika Produksi Perspektif Maqashid As-Syariah - Irkham Firdaus, Muhammad; Reyhan, Muhammad (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2022)
Production is one of the most important economic activities. Production is also an important factor in determining company profits, because production is an activity or process in the manufacture of goods and services, which aims to meet the needs of the community. The goods or services produced can be in the form of primary, secondary and tertiary needs. In the production process, there must be good principles and ethics, as in Islamic economics, that the principles and ethics of production must have noble aims, namely meeting consumer needs, no one is harmed, goods and services must be halal. The Qur'an defines production as a link in the chain of consumption and distribution. So without production activities, economic activity will stop and die. So the essence of production activities in Islamic economics is to achieve the goal of maslahah, namely the public interest in meeting the needs of the community, by taking profits that are in accordance with production costs, and not aiming to achieve satisfaction, because if the highest point is satisfaction, then a producer will do everything he can. way of doing production.